Honoring of an outstanding scientist and naturalist J.K.Paczoskiin Kherson (Ukraine) (to the 150th anniversary of his birth) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
Honoring of an outstanding scientist and naturalist J.K.Paczoskiin Kherson (Ukraine) (to the 150th anniversary of his birth)